A Study on Physical, Morphological and Antibacterial Properties of Bio Polymers Reinforced Polyvinyl Acetate Foams - Nadir Yildirim (1664650) (2022)
In this study, foaming-agent free novel polyvinyl acetate (PVAc) foams reinforced with bio polymers were manufactured through freeze-drying technique. The physical, morphological and antibacterial properties of foams which were reinforced with different ratio of zinc borate and water-soluble chitosan were investigated according to relevant standards. The PVAc foams showed low densities (0.12 g/cm3 – 0.21 g/cm3) and high porosity rates (87.50% - 79.05%). The results showed that although the foams have no antibacterial character against Escherichia Coli, they have antibacterial character against Staphylococcus Aureus bacteria. This study mainly focusses on physical and morphological properties of the foams. However, researchers also performed accelerated weathering tests to determine its usability in different industries. The effects of accelerated weathering on the surface of foams were investigated by measuring surface color. The highest color difference was determined 8.09. This foam can be used as a low-density packaging material and/or medical box with its promising physical and morphological properties with hazardous-chemical free structure. Other Information Published in: Materials Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1590/1980-5373-mr-2021-0579 Additional institutions affiliated with: Office of Innovation and Industrial Relations - HBKU